PENGARUH PERILAKU KEPEMIMPINAN, KOMPETENSI PROFESIONAL DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA GURU (Studi Pada SMA Se-Kecamatan Batalaiworu Kabupaten Muna) - Wa Ode Sarpan; La Hatani; Nursaban Rommy Suleman (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this research is to test and explain the influence of leadership behavior, professional competence and non-physical work environment on teacher performance. This research approach is quantitative with a positivist paradigm. Data was collected by cross-section by using a questionnaire. The population of this study were all 141 teachers at SMA in Batalaiworu District, Muna Regency. The sample size was determined using a purposive sampling technique, namely teachers who were civil servants (PNS), so that a sample of 118 people was obtained. The analytical tool used is Multivariate Regression Analysis. The results showed that leadership behavior, professional competence and non-physical work environment simultaneously had a positive and significant effect on teacher performance. Then leadership behavior partially positive and significant effect on teacher performance. Professional competence partially has a positive and significant effect on teacher performance. and the non-physical work environment has a positive and significant effect on teacher performance. This means that the more leadership behavior, professional competence and non-physical work environment increase, the teacher's performance will increase significantly.